2021
DOI: 10.1093/jxb/erab262
|View full text |Cite
|
Sign up to set email alerts
|

The protein modifier SUMO is critical for integrity of the Arabidopsis shoot apex at warm ambient temperatures

Abstract: SUMO is a protein modification whose conjugate levels peak during acute heat stress. We find that SUMO is also critical for plant longevity when Arabidopsis experiences a prolonged non-damaging period of only 28 degrees Celsius. Remarkably, this thermo-lethality at 28 degrees was not seen with any other mutant of the SUMO pathway tested. Autoimmunity due to low SUMO1/2 expression levels was not causal for this thermo-lethality. The role of SUMO for thermo-resilience was also distinct from its requirement for t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…SUMOylation acts in a novel role, mediating the transcription switch mechanism between development and HS in plant cells by targeting different proteins (Han et al 2021). The interconnected dual role for SIZ1 and SUMO1/2 conjugation in the switch between plant immunity and high temperature-induced growth also supports this view (Hammoudi et al 2018(Hammoudi et al , 2021. In general, SUMOylation is vital for survival in stressful situations because it enables a swift reaction to a changing environment.…”
Section: Sumoylation Rapidly Controls Transcription Under High Temper...mentioning
confidence: 76%
See 1 more Smart Citation
“…SUMOylation acts in a novel role, mediating the transcription switch mechanism between development and HS in plant cells by targeting different proteins (Han et al 2021). The interconnected dual role for SIZ1 and SUMO1/2 conjugation in the switch between plant immunity and high temperature-induced growth also supports this view (Hammoudi et al 2018(Hammoudi et al , 2021. In general, SUMOylation is vital for survival in stressful situations because it enables a swift reaction to a changing environment.…”
Section: Sumoylation Rapidly Controls Transcription Under High Temper...mentioning
confidence: 76%
“…Van den Burg et al found that SUMO-dependent thermo-resilience can be potentially controlled in a different manner. SUMO1/2 activates temperature acclimation via the master regulator of heat stress: the HSFA1 family (Hammoudi et al 2021 ). This finding explained that SUMO1/2 have key roles in enabling plants to withstand prolonged warm periods.…”
Section: Sumoylation Rapidly Controls Transcription Under High Temper...mentioning
confidence: 99%
“…Newer investigations have revealed that SUMO1/2 activation contributes to temperature acclimation through the HSFA1 family, recognized as the principal orchestrator of heat stress responses. Notably, mutant lines lacking SUMO1/2 exhibit thermosensitivity at 28 • C [169]. In a recent discovery by Zhang et al [168], an additional E3 ligase, the XB3 ortholog in Arabidopsis thaliana (XBAT31), has been identified.…”
Section: Role In Heat Stressmentioning
confidence: 99%
“…Another post-translational modification that is important in temperature signalling is SUMOylation. While SUMOylation is required for thermomorphogenesis and thermotolerance, SUMO-dependent thermoresilience is potentially controlled in a different way compared with the protein damage pathway that underpins thermotolerance (Hammoudi et al, 2021).…”
Section: Temperature Signalling Networkmentioning
confidence: 99%